(untitled) (SAARC Journal of Agriculture, 2024)
Rice is cultivated through mechanical transplanting or direct seeding methods worldwide. Our investigation focused on evaluating the performance of mechanical transplanting and surveying yield, and yield components. The study was conducted at the Yamagata University Faculty of Agriculture at the Takasaka Farm. A Kubota (NSU-87) transplanter with ‘Heanuki’ rice seedlings was used. We evaluated the performance of the transplanter by the ratio of the effective field capacity (hah-1) to the theoretical field capacity (hah-1). The average field capacity and efficiency of the eight rows of self-propelled paddy transplanter was 0.184 ha/h and 76.6%, respectively, with an area of 0.024 ha at an average operating speed of 1 km/h. The average planting depth (30.36 mm), number of seedlings per hill (3.66), number of seedlings per square meter (102.16), and hill-to-hill distance (15.09 cm) were surveyed and measured. The average grain yield (5.5 tons/ha) was calculated. The average values of (411.2) panicles per square meter, (68.4) grains per panicle, (89.6) percent of filled grains, and (22.25) 1,000-grain weight were obtained. Kubota type (NSU-87) transplanter was satisfactory, at the parameters of fieldwork capacity, fieldwork accuracy, grain yield, and yield components. A self-propelled transplanter is essential for rice cultivation, and it is recommended for saving the amount of seed, ease (weed control and field monitoring), easy operation system, and better crop stand establishment. SAARC J. Agric., 22(1): 153-167 (2024)